LITERATUR REVIEW TREND PENELITIAN ADVENTURE GAMES UNTUK PEMBELAJARAN IPAS DI SEKOLAH DASAR TAHUN 2020-2025 - Noor Aini, Alfina; Widiyatmoko, Arif; Sri Wardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the trends in the use of adventure games in Natural and Social Science (IPAS) learning in Indonesian elementary schools from 2020 to 2025.The background of this research lies in the importance of developing interactive and contextual learning media. The method employed is a Systematic Literature Review (SLR), with data obtained through the Publish or Perish (PoP) application. The analyzed articles were selected based on inclusion criteria, namely being indexed in Google Scholar, discussing the use of adventure games in IPAS learning, and being published between 2020 and 2025. A total of 500 articles indexed in Google Scholar were initially identified. After eliminating 390 articles that were irrelevant to the research keywords, 50 articles were screened based on their titles and abstracts. Subsequently, 13 articles were deemed eligible for analysis. An additional 37 articles were excluded because they were undergraduate theses or dissertations and considered less suitable for analysis. In total, 13 journal articles and 3 proceedings were analyzed that met the criteria for studies on the trend of adventure games in IPAS learning. The findings indicate that publication trends have fluctuated, with Universitas Negeri Surabaya identified as the most productive institution. Adventure games are utilized to enhance literacy skills, learning outcomes, critical thinking abilities, and student motivation, with learning materials covering topics such as endangered animals, the human circulatory system, force and motion, and changes in the state of matter. These findings suggest that adventure games are effective in supporting IPAS learning that is more exploratory and meaningful. This study contributes to the development of innovative, technology-based learning media for future educational practices. Keywords: adventure games, natural and social science (IPAS), elementary school, systematic literature review, research trends